Site-specific DNA transesterification catalyzed by a restriction enzyme - Sasnauskas, Giedrius (National Academy of Sciences, 2007)
Most restriction endonucleases use Mg(2+) to hydrolyze phosphodiester bonds at specific DNA sites. We show here that BfiI, a metal-independent restriction enzyme from the phospholipase D superfamily, catalyzes both DNA hydrolysis and transesterification reactions at its recognition site. In the presence of alcohols such as ethanol or glycerol, it attaches the alcohol covalently to the 5′ terminus of the cleaved DNA. Under certain conditions, the terminal 3′-OH of one DNA strand can attack the target phosphodiester bond in the other strand to create a DNA hairpin. Transesterification reactions on DNA with phosphorothioate linkages at the target bond proceed with retention of stereoconfiguration at the phosphorus, indicating, uniquely for a restriction enzyme, a two-step mechanism. We propose that BfiI first makes a covalent enzyme–DNA intermediate, and then it resolves it by a nucleophilic attack of water or an alcohol, to yield hydrolysis or transesterification products, respectively.